2023
DOI: 10.1186/s13063-023-07829-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct letters to relatives at risk of hereditary cancer—study protocol for a multi-center randomized controlled trial of healthcare-assisted versus family-mediated risk disclosure at Swedish cancer genetics clinics (DIRECT-study)

Carolina Hawranek,
Hans Ehrencrona,
Anna Öfverholm
et al.

Abstract: Background The results of germline genetic testing for hereditary cancer are of importance not only to the patients under investigation but also to their genetic at-risk relatives. Standard care is to encourage the proband (first family member under investigation) to pass on this risk information to the relatives. Previous research suggests that with family-mediated disclosure, only about a third of at-risk relatives contact health care to receive genetic counselling. In some studies, compleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The direct letters were sent with registered mail and included information on the cancer risk assessment conducted in the family and possible implications for the ARRs. Further details of the study, including templates of the letters, are found in the published study protocol [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The direct letters were sent with registered mail and included information on the cancer risk assessment conducted in the family and possible implications for the ARRs. Further details of the study, including templates of the letters, are found in the published study protocol [ 11 ].…”
Section: Methodsmentioning
confidence: 99%